Improving outcomes in veterans with oropharyngeal squamous cell carcinoma through implementation of a multidisciplinary clinic. Issue 6 (29th March 2017) - Light, Tyler; Rassi, Edward El; Maggiore, Ronald J.; Holland, John; Reed, Julie; Suriano, Kathleen; Stooksbury, Marcelle; Tobin, Nora; Gross, Neil; Clayburgh, Daniel
Abstract: Background: Treatment of head and neck cancer is complex, and a multidisciplinary clinic may improve the coordination of care. The value of a head and neck multidisciplinary clinic has not yet been established in oropharyngeal squamous cell carcinoma (SCC). Methods: A retrospective review was conducted of Veterans Affairs patients with oropharyngeal SCC undergoing concurrent chemoradiation before and after implementation of the head and neck multidisciplinary clinic. Results: Fifty‐two patients before and 54 patients after multidisciplinary clinic were included in this study. Age, tobacco use, and p16+ status were similar between groups. With multidisciplinary clinic, time to treatment decreased, and utilization of supportive services, including speech pathology, dentistry, and nutrition increased. The 5‐year disease‐specific survival rate increased from 63% to 81% ( p = .043) after implementation of the multidisciplinary clinic. Multivariate analysis showed that disease stage ( p = .016), p16 status ( p = .006), and multidisciplinary clinic participation ( p = .042) were predictors of disease‐specific survival. Conclusion: Implementation of a multidisciplinary clinic improved care coordination and disease‐specific survival in patients with oropharyngeal SCC. © 2017 Wiley Periodicals, Inc. Head Neck 39: 1106–1112, 2017